Socio-economic status and health awareness are associated with choice of cooking oil in Costa Rica - Colón Ramos, Uriyoán (2007)
Objective To examine the socio-economic and lifestyle determinants of cooking oil choice in Costa Rica during the last decade (1994–2004). Design Cross-sectional study. Subjects (total n = 2274) belonged to the control population of a large case–control study; they were recruited yearly. Data about type of oil used for cooking, dietary intake, socio-economic and demographic characteristics were collected. Setting A dietitian visited all subjects and conducted the interviews at their homes; all subjects lived in the Costa Rican central valley region. Subjects Adult, free-living, rural and urban Costa Ricans with no history of myocardial infarction and physical or mental disability. Results The odds of choosing soybean over palm oil increased significantly each year (P < 0.05) and was determined by high socio-economic status (SES) and variables that suggest health awareness (self-reported history of hypertension, high cholesterol, multivitamin use and intake of green leafy vegetables). The odds of choosing other unsaturated oils, namely corn and sunflower, over soybean oil also increased yearly (P < 0.05) and was associated with the same two factors (high SES and health awareness). Palm oil users remained in the lowest SES tertile and were more likely to live in rural areas. Across all SES tertiles, high health awareness determined the odds of choosing other unsaturated oils over palm oil, and soybean oil (P < 0.05). Conclusion These data show that, in addition to SES, health awareness is associated with the selection of unsaturated oils over palm oil in a developing country undergoing transition. These data should be considered when targeting nutrition messages and policies that promote better dietary choices.